(untitled) (Web of Discoveries: Journal of Analysis and Inventions, 2025)
The issue of increasing the capacity of fiber-optic transmission systems is relevant and has prospects for development in the future. The article discusses methods for increasing capacity and their scope of application, and also describes a method for increasing the capacity of fiber-optic transmission systems using Y-splitters.